2006
DOI: 10.1007/s11130-006-0026-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Antimutagenic, Antioxidant and Enzymatic Activities of Methanolic Extract from Common Beans (Phaseolus vulgaris L)

Abstract: Common beans are rich in phenolic compounds, which can provide health benefits to the consumer. The objective of this work was to study the relationship among antimutagenicity, antioxidant and enzymatic activities of methanolic extract and trolox by principal components multivariate analysis. Antimutagenicity of phenolic compounds present in methanolic extract from the seed coat of common beans (P. vulgaris, Flor de Mayo Bajío cultivar) and trolox against AFB1 mutagenicity were evaluated in the Salmonella typh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…The polyphenol extraction was performed according to CardadorMartínez et al [6]. Five extractions were performed for each treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The polyphenol extraction was performed according to CardadorMartínez et al [6]. Five extractions were performed for each treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Dry legumes are a good source of bioactive polyphenols [4] and also contribute to polyphenol intake from other foods [5]. The antioxidant capacity [6] and the antimutagenic [7][8][9][10], apoptosis-related [11] and antiproliferative effects of legumes are associated with the presence of phenolic compounds [12,13]. The abundance of phenolic compounds in such legumes as the common bean (Phaseolus vulgaris) [9], faba (broad) bean (Vicia faba) [14,15], beach pea (Lathyrus maritimus) [16], Total Phenolic Content and Antioxidant Activity of Chickpea (Cicer arietinum L.) as Affected 725 by Soaking and Cooking Conditions mung bean (Vigna radiata) [17], lentil (Lens culinaris) [18] and chickpea (Cicer arietinum) [19][20][21][22] implies that they may be significant food sources of active antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Various recent reports state that the natural antioxidants may reduce or inhibit the mutagenic potential of mutagens and carcinogens (Cardador-Martínez et al, 2006;El-Sayed & Hussin 2013). Zahin et al (2010) have reported that the anticarcinogenic and antimutagenic activities of medicinal and food plants are executed mainly by scavenging of free radicals.…”
Section: Discussionmentioning
confidence: 99%